Does One Design Fit All? On The Transferability Of The PJM Market Design To The German Electricity Market - Katrin Schmitz; Christoph Weber (University of Duisburg-Essen, Chair for Management Science and Energy Economics, 2013)
Germany's nuclear phase out and an increasing share of fluctuating RES production amplifies the North-South congestion problem in the German electricity grid. But congestion management becomes a serious issue not only in the German but in the whole European electricity system as German wind production does not only affect the German grid. In theory it is well established that nodal pricing is the most efficient congestion management method. In literature the PJM well-established nodal market design often serves as a reference and is viewed as benchmark. To benefit from experiences made in the U.S. the transfer of the PJM market design to Germany could be advantageous. This article compares key elements of the generation mix, the network structure, the cross-border interconnection as well as the congestion situation of both electricity markets to assess potentials and impediments for an implementation of the PJM nodal market design in Germany. We show that both markets are less different in structure than expected but that large differences in performance respectively in congestion frequency lead probably to much lower welfare gains. Transfer of the PJM market design to Germany is possible in principle, but adjustments to RES would be advantageous.
Keywords: 330; Nodal Pricing; Market Design; Electricity Markets